2014
DOI: 10.1111/ene.12512
|View full text |Cite
|
Sign up to set email alerts
|

The course of headache in idiopathic intracranial hypertension: a 12‐month prospective follow‐up study

Abstract: Although headache in 43% of patients responded well to ICP management, sustained long-term headache was seen in the remaining patients, despite resolution of papilledema. Headache in IIH may thus be attributed to more complex mechanisms than ICP elevation alone. High ICP and young age were associated with better headache outcome. Early treatment according to standard guidelines seems sufficient to ensure excellent visual outcome in the vast majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 22 publications
11
71
2
6
Order By: Relevance
“…In our IIH populations of 44 and 40 patients, respectively, the visual function were almost normalized in all subjects after 12 months whereas the major long-term complications were headache and impaired cognition [Yri et al 2014b;Yri et al 2012]. Despite the severe headache and a potential treat to visual function, compliance to treatment and follow-up is surprisingly poor.…”
Section: Headache Management and Prognosismentioning
confidence: 71%
See 1 more Smart Citation
“…In our IIH populations of 44 and 40 patients, respectively, the visual function were almost normalized in all subjects after 12 months whereas the major long-term complications were headache and impaired cognition [Yri et al 2014b;Yri et al 2012]. Despite the severe headache and a potential treat to visual function, compliance to treatment and follow-up is surprisingly poor.…”
Section: Headache Management and Prognosismentioning
confidence: 71%
“…In the recent study predictors for a favorable outcome of headache 12 months after diagnosis were younger age at onset and a high diagnostic opening pressure. This may relate to an early diagnosis or fast initiation of relevant treatment in these patients [Yri et al 2014b]. …”
Section: Headache Management and Prognosismentioning
confidence: 99%
“…Many IIH patients have persistent headache despite normalized intracranial pressure 11 . A recent prospective study similarly found that 57% of patients with IIH had sustained, long-term headache despite resolution of papilledema 12 . Likewise, studies of CSF shunting for IIH elated headaches confirm the notion that long-term headache control is frequently independent of CSF pressure management with a 50% headache recurrence rate in three years 13 .…”
Section: Discussionmentioning
confidence: 94%
“…Features consistent with migraine, including unilateral throbbing, with nausea and photophobia are also reported 44. Back pain, neck pain and radicular pain frequently occur 45…”
Section: Clinical Featuresmentioning
confidence: 99%